Hospitalization for Acute Respiratory Tract Infection in a Low-Antibiotic-Prescribing Setting: Cross-Sectional Data from General Practice - Christin Löffler; Attila Altiner; Annette Diener; Reinhard Berner; Gregor Feldmeier; Christian Helbig; Winfried V. Kern; Anna Köchling; Michaela Schmid; Gerhard Schön; Helmut Schröder; Karl Wegscheider; et al. (Antibiotics, 2020)
Background: Acute respiratory tract infections (ARTI) are the main cause of inappropriate antibiotic prescribing. To date, there is limited evidence concerning whether low levels of antibiotic prescribing may impact patient safety. We investigate whether antibiotic prescribing for patients seeking primary care for ARTI correlates with the odds for hospitalization. Methods: Analysis of patient baseline data (n = 3669) within a cluster-randomized controlled trial. Adult patients suffering from ARTI in German primary care are included. The main outcome measure is acute hospitalization for respiratory infection and for any acute disease from 0 to 42 days after initial consultation. Results: Neither the antibiotic status of individual patients (OR 0.91; 95% CI: 0.49 to 1.69; p-value = 0.769) nor the physician-specific antibiotic prescription rates for ARTI (OR 1.22; 95% CI: 1.00 to 1.49; p-value = 0.054) had a significant effect on hospitalization. The following factors increased the odds for hospitalization: patient’s age, the ARTI being defined as lower respiratory tract infections (such as bronchitis) by the physician, the physician’s perception of disease severity, and being cared for within group practices (versus treated in single-handed practices). Conclusions: In a low-antibiotic-prescribing primary care setting such as Germany, lack of treatment with antibiotics for ARTI did not result in higher odds for hospitalization in an adult population.